Freeze-Fracture Surface of Salivary Glands of Rat Observed by Scanning Electron Microscopy - Espinal, E. G.; Ubios, Ángela M.; Cabrini, Rómulo Luis (S. Karger AG. Basel, 1983)
Fil: Espinal, E. G. Comisión Nacional de Energía Atómica; Argentina